Case report: One case of acute myeloid leukemia M3 with atypical morphology - Fa-Sheng Liu; Hua-Liang Huang (Frontiers in Oncology, 2024)
Acute promyelocytic leukemia (APL) is a type of acute myeloid leukemia. About 2% of APL is characterized by atypical rearrangements. Here we reported one APL case with atypical manifestations and morphology. A 35-year-old woman patient, mainly due to fatigue, poor appetite for over 10 days and intermittent fever for 3 days. combined with the results of flow cytometry, fusion gene and chromosome, the patient was diagnosed as AML-M3 with atypical morphology. Double induction therapy with retinoic acid and arsenous acid was immediately administrated. Idarubicin was administrated on the 18th day. A re-examination was performed in the 5th week, both the blood routine test and myelogram showed normal results, and the fusion gene turned negative, indicating complete remission. When atypical morphology occurs, peripheral blood POX staining may be performed to check the abnormal cells. Flow cytometry, chromosome analysis, and fusion gene analysis are also required for further diagnosis.